On the Development of Climate Data Visualization tool for Interpretation of Empirical Results from Climate Model: Does it add Value to Different Stakeholders? - Sanga, Camilius; Sumari, Neema; Tumbo, Siza (My University, 2013)
In time of climate change there is a lot of interest in communicating detailed information and knowledge pertaining to climate to different stakeholders. In order to aid informed decision making related to changing climate and weather variability there is need for data visualization tool. Data visualization tool plays a great role in interpreting bulk climate information produced or collected from different districts, regions and nations at large. In Tanzania, online real-time data visualization tool can help to bridge the gap in the current system whereby climate information is disseminated using television, radio as well as face-to face. These methods have many problems, one being difficulty for end user to aggregate the disseminated climate information over long period of time. This paper seeks to present a work toward developing of a tool for such purpose. The work was done by Database for Crop Models Simulation team from Tanzania with consultation of team members from Kenya, Uganda and Ethiopia. It is anticipated that the tool will enhance efficiency and effectiveness in dissemination and communication of climate information and knowledge to all actors who need it. Furthermore, the results from this study will simulate the debate about climate data visualization in this era where the climate change is a problem which needs to be mitigated using a state-of-art solution.
Keywords: climate; modelling; information; knowledge; dissemination; communication; visualization tool